Study on high temperature corrosion mechanism of water wall tubes of 350 MW supercritical unit. (March 2021) - Sun, Xu; Ning, Yuheng; Yang, Jian; Zhao, Yong; Yang, Zhanjun; Zhou, Xuzhe
Highlights: The high-temperature corrosion products have three layers structure. There is a surge of sulfur content in the intermediate layer. Coal quality and boiler combustion method determine the high temperature corrosion. Abstract: The water wall of a 350 MW supercritical unit was severely corroded at high temperature in a short period. An analysis was made on the mechanism of high temperature corrosion of the water wall by chemical analysis, metallographic examinations, mechanical property test, and SEM observation. The results show that high temperature corrosion has no obvious effect on the material properties, and the main failure form is the reduction of tube wall by corrosion. Through the structure and composition analysis of corrosion products, it is found that there are three corrosion product layers on the outer wall of the water wall. Lots of holes existed between the corrosion product layer and the matrix, which made the corrosion product is easy to be spalled. The sulfur content in the corrosion product increases gradually from inside to outside, which proves that sulfur is the main factor affecting the high temperature corrosion of the water wall.